In Silico and Biological Evaluation of N‐(2‐methoxyphenyl) Substituted Pyrazoles Accessed via a Sonochemical Method. Issue 4 (26th January 2021) - Venkata Basaveswara Rao, Mandava; Veera Durga Rao, Bodapati; Vijaya Vardhini, Suryadevara; Nagendra Kumar, A. V. D.; Rao Gorja, Dhilli; Kapavarapu, Ravikumar; Pal, Manojit
Abstract: In view of remarkable biological properties including anticancer activities of N ‐aryl pyrazoles we have explored N ‐(2‐methoxyphenyl) substituted pyrazoles and related derivatives as potential cytotoxic agents. In silico methods were adopted to understand/predict the biochemical and physiological effects, toxicity, and biological profiles of these compounds thereby assessing the potential drug‐likeness of the hit molecule. The target compounds were conveniently prepared via a sonochemical method involving the C−N bond forming reactions in the presence of CuI in DMSO. A library of N ‐aryl pyrazole derivatives were synthesized via coupling of iodoarenes with pyrazole whereas the use of other N ‐heteroarene such as imidazole and pyrrole in place of pyrazole afforded the corresponding product. The in   vitro evaluation of all these compounds was carried out against MDAMB‐231 and MCF‐7 cell lines and subsequently against SIRT1. The pyrazole derivative 3  c showed encouraging growth inhibition of both MDAMB‐231 and MCF‐7 cell lines (59 and 48 % at 10 μM, respectively) and inhibition of SIRT1 (IC50 ∼ 6.21±0.42 μM) in   vitro . The molecular docking studies suggested H‐bonding (involving OMe group), Van der Waals and hydrophobic interactions of 3  c with important amino acid residues in the catalytic domain of SIRT1. Overall, cell‐based as well as enzyme assay, molecular modelling, in silico ADME/TOX prediction and in   vitro stability studies suggested 3  c as a potential hit molecule. Abstract : The N ‐(2‐methoxyphenyl)pyrazoles were explored as potential cytotoxic agents. In silico approaches were adopted to understand and predict biological profiles of this class of compounds. These compounds were conveniently prepared via a sonochemical method involving the C−N bond forming reactions in the presence of CuI in DMSO. Cell/enzyme‐based assays, molecular modelling, in silico and in   vitro stability studies suggested 1‐(4‐methoxy‐[1, 1′‐biphenyl]‐3‐yl)‐1 H ‐pyrazole (3  c) as a potential hit molecule.